Etiology of Acute Diarrhea in Tunisian Children with Emphasis on Diarrheagenic Escherichia coli: Prevalence and Identification of E. coli Virulence Markers. - Imen Ben Salem-Ben Nejma; Mouna Hassine Zaafrane; Fredj Hassine; Khira Sdiri-Loulizi; Moncef Ben Said; Mahjoub Aouni; Ridha Mzoughi (Tehran University of Medical Sciences, 2014)
Diarrheal diseases can be caused by viral, bacterial and parasitic infections. This paper provides a preliminary image of diarrhea with regards to etiology and epidemiologic factors in Tunisian children less than five years of age.Overall, 124 diarrhoeal stools were collected from patients suffering from acute diarrhea and 54 stool samples from healthy children. All stools were examined for the presence of enteric pathogens.In diarrheagenic children, 107 pathogenic bacteria were isolated (12 Salmonella spp. (9.7%) and 95 diarrheagenic Escherichia coli strains (76.6%): 29 enteroaggregative E.coli (EAEC) (23.4%), 15 enteroinvasive E.coli (EIEC) (12.1%), 17 enteropathogenic E.coli (EPEC) (13.7%), 26 enterotoxigenic E.coli (ETEC) (21%) and 2 enterohemoragic E.coli (EHEC) (1.6%). However, in the control group, 23 pathogenic E.coli strains were isolated (42.6%): 8 EAEC (14.8%), 12 EIEC (22.2%) and 3 EPEC (5.5%). Among diarrheagenic E.coli (DEC), only ETEC strains were significantly recovered from diarrheagenic children than from healthy controls (P < 0.0003). Group A rotavirus was identified in 33.9% (n=42) of diarrheagenic children and in 11.1% among the control group (n=6). Concerning norovirus, 8.9% (n=11) of the samples collected from diarrheagenic children and 9.2% (n=5) from the control group were positive. The prevalence of rotaviruses and Salmonella spp were also significantly higher in patients with diarrhea than in controls (P = 0.002 and P < 0.019, respectively). Finally, enteropathogenic parasites (Entamoeba coli and cryptosporidium Oocystes) were isolated from 4.8% and 9.2% of diarrheagenic and control children, respectively.These results provide baseline data about the relative importance of different enteropathogens in Tunisian children.